Analysis Of The Relationship Between Wealth Added And Environmental, Social, And Governance (Esg) Risk On Stock Prices - Irewati, Titiek (Journal Research of Social Science, Economics, and Management, 2025)
The dynamics of stock prices have always been a point of concern for investors who invest in a public company. Theoretically, there are internal and external factors that play a role in stock price fluctuations. This study examines internal factors, namely the company's performance expressed as Wealth Added value and the level of Environmental, Social and Governance (ESG) risk as independent variables and its Effect on Stock Price as dependent variables. The observation sample was selected from a group of corporate companies included in the Wealth Added SWA100 index published in 2024. Data from 20 samples of public companies in the material, energy and utility sectors were tested by Multiple Linear Regression analysis, and the results were that there was no significant influence of Wealth Added value and ESG risk on stock prices. The test/correlation showed a positive trend between the value of Wealth Added and the stock price and the negative direction between the level of ESG risk and the stock price.